Promoting Inclusive Growth in the Middle East and North Africa: Challenges and Opportunities in a Post-Pandemic - Cardarelli, Roberto; Martin, Mercedes Vera; Lall, Subir (Washington, D.C International Monetary Fund (IMF), 2022)
"Despite some pre-pandemic gains in poverty reduction, literacy, and lifespans, many economies in the Middle East and North Africa (MENA) have struggled to ensure that the benefits of economic development and diversification accrue equitably to all segments of their populations. Among the main issues that remain unresolved are the high share of inactive youth (who are not engaged in employment, education, or training); large gaps in economic opportunities for women; fragmented social protection systems; and underdeveloped private sectors with tight regulation, absence of a level playing field, and limited access to credit that stifle the creation of new firms and growth, employment, and incomes. The COVID-19 pandemic not only risks wiping out some of the progress made in the region over the past decades, but could also exacerbate inequality in a durable way. There is evidence that the impact of the pandemic has been uneven across groups, with the recession having a disproportionate effect on the low-skilled, the young, women, and migrant workers in employment and incomes. With widespread inequality, high unemployment, and the expected entry of 27 million young people into the labor force over the next 10 years, countries across the MENA region need to evolve their economic models to boost job creation and make sure that the benefits of economic development are shared more widely among all their citizens. This book’s objective is to reassess the inclusive growth agenda in the MENA region in light of the rapidly changing pandemic-influenced world. It argues that countries need to embrace global trade and technological advances and evolving demographics at home as an opportunity to successfully implement policies that foster higher and more inclusive growth. It underscores that a return to the old social contract is neither desirable nor feasible. The book presents a comprehensive view of policies suited to the regional context that would boost job-rich and inclusive growth within a resilient macroeconomic policy framework. Its goal is to provide guidance to policymakers in the region to frame how best to promote inclusive growth, including in their engagement with all stakeholders". (IMF page)
Foreword -- Introduction/Roberto Cardarelli • Mercedes Vera Martin • Subir Lall -- 1. Defining and Measuring Inclusive Growth in the MENA Region/ Aidyn Bibolov • Yang Yang • Jiayi ma -- 2. Inclusiveness, Growth, and Stability/ Chiara Maggi • Xin Tang -- 3. Fostering Private-Sector-Led Growth in the MENA Region: A New Role for the State/ Suchanan Tambunlertchai • Monica Petrescu • Mahdi Ansari -- 4. The Changing Nature of Work: Improving the Functioning of Labor Markets/ Sidra Rehman • Agustin Velasquez -- 5. Addressing Gender Gaps in MENA Labor Markets/ Hippolyte Dalima • Diego Gomes -- 6. Improving Human Capital in the MENAP Region through Adequate and Efficient Social Spending/ Anastasia Guscina -- 7. Financial Inclusion/ Anta Ndoye • Adolfo Barajas -- 8. Moving from Aspiration to Action on Climate Adaptation/ Gareth Anderson -- Index
"This book is part of the preparatory work for the IMF and World Bank Annual Meetings that are scheduled to take place in Marrakech in October 2023.”
Includes bibliographical references and index.
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC CONDITIONS; ECONOMIC POLICY; LABOUR MARKET; Financial inclusion; MENA Region